Investigation into the Roles of Agents in Supporting Students Working on Group Projects Online - Whatley, Janice; Beer, Martin (Proceedings of the International Conference on Networked Learning, 2002)
Group projects give students an opportunity to discuss their understanding of the subject with their peers, as they apply the theory to practice. We should try to incorporate an element of groupwork in online learning and teaching provision, but it is difficult to simulate some of the processes of groupwork online. In this paper we present initial work on developing a software agent which can help in supporting students working online on group projects. This agent is to be incorporated into a learning environment being used to support the OTIS learning and teaching provision. The implementation is described together with its potential for enhancing the support given to online learners.